Propriedades de armazenagem de hidrogênio do intermetálico TiFe processado por moagem de alta energia e laminação a frio sob atmosfera controlada - Romero Vega, Luis Esteban (2017)
TiFe is a material of practical interest for hydrogen storage due to its absorption capacity of ~ 1.9 wt. % H at room temperature and the relative low cost of its constituent elements. However, this intermetallic requires a process of thermal activation to absorb hydrogen, in order to overcome the deleterious effects of the contamination of the material by atmospheric oxygen. Thermal activation processes can be long and complex. In order to avoid them, in this study two processing routes were designed: (1) mechanical alloying to obtain TiFe from the constituent powders, and (2) Cold Rolling under inert atmosphere of the intermetallic TiFe processed by arc melting. In this study, a new processing strategy was investigated: pre-milling Ti and Fe powders with the purpose of preparing superficially the milling vial and then a new milling of these elements in the presence of stearic acid. This strategy generated good material recovery after 2 hours of milling and low oxygen contamination. In addition to that, H-absorption capacities of 0.9; 1.0; 1.1 and 1.2 wt. % H2 (room temperature and 20 bar of H2), were obtained for processing times of 2, 6, 10 and 20 h, respectively, without using a thermal activation process. On the other hand, after cold rolling under inert atmosphere of the intermetallic TiFe processed by arc melting, it was observed a fast absorption of hydrogen (room temperature and 20 bar of H2) without the use of a thermal activation process, obtaining absorption capacities of: 1.4 wt. % H2 in the powder and in the flake after 20 passes and 1.4 wt. % H2 in the powder and 1.3 wt. % H2 in the flake after 40 passes.